PENGEMBANGAN MEDIA KOMIK BAHAN AJAR IPA TERPADU KELAS VIII SMP NEGERI 3 SAROLANGUN - Juwati -; Hj. Hidayati (Universitas Sarjanawiyata Tamansiswa, 2017)
This study aims to develop device learning according to a model learning media comic of teaching materials in subchapter mechanical systems man and its relation to health in the class viii junior high schools 3 Sarolangun. The kind of research is research development referring to the model of development borg and gall. Subject research used as a subject pilot were students class VIII junior high schools 3 Sarolangun. Steps research is: analysis products to be developed, product development early, validation the people of and revision products, pilot the field limited and revision products, trial on center court and the final product. Media developed tested its feasibility with the validation by the matter and media experts before undergone a try. An instrument used to collect data is chief. The results of the study showed that validation the people of material obtain the average score 4.10 included in 23.501 very good. The results of validation media experts have the average score 3.9 included in category good.The results of response students to media learning comic obtain the average score the percentage value of 93,04 included in category good.